Organizational Culture and Quality Improvement on Sustainability Performance During the First Year of Covid-19 in the Healthcare Industry - Morgan, Yun-Chen; Zee, Susan M. L.; Fok, Lillian Y. (Journal of Applied Business and Economics, 2023)
This research examines employees’ perceptions of green practices implemented in organizations and their impacts on sustainability performance focusing on the healthcare industry during the first year of COVID-19. It explores how organizational culture and quality improvement practices affect the relationship between green practices and sustainability performance. Results indicate a multi-level framework that organizational culture and quality improvement practices significantly affect the relationship between green practices and healthcare organizations’ sustainability performance.